A new model to determine the shear modulus and Poisson's ratio of shock-compressed metals up to the melting point. Issue 4 (2nd October 2021) - Kraus, E. I.; Shabalin, I. I.
ABSTRACT: In this paper, using the few-parametric equation of state, an approach is implemented to the calculation of the longitudinal and bulk sound speeds, as well as the elastic moduli of a number of isotropic metals behind the front of a strong shock wave. The results of theoretical calculations for aluminum are compared with the available shock impact experimental data. A new analytical approximation of the dependence of the Poisson's ratio on the pressure is proposed for metals. Non-monotonic dependence of the shear modulus for uranium on the pressure and temperature in view of the melting behind the shock front is determined.